Emergy Analysis of a Biomass Direct-fired Power Plant in Inner Mongolia of China - Pang, Mingyue; Zhang, Lixiao; Wang, Changbo; Liu, Gengyuan (Journal of Environmental Accounting and Management, 2026)
Though encouraged by a series of policies and measures, the biomass direct-fired power generation industry in China has not achieved expected rapid development, like other renewable electricity industries such as small hydropower, photovoltaic power and wind power. In this paper, an emergy analysis was performed to evaluate the overall performance and relative environmental sustainability of biomass direct-fired power production systems, taking a plant in Inner Mongolia as an example. The evaluation results show that the solar transformity of biomass direct-fired electricity in 2011 is 1.14E+05 seJ/J, similar to that of typical renewable electricity technologies and much lower than that of fossil fuel power plants. The comparison between the emergy-based indicators with those of other electricity production systems also confirms the outstanding performance of the biomass direct-fired power system, indicating that biomass direct-fired power technology itself is relatively well established in China now. However, one of the key constraints to the healthy development of the biomass direct-fired power industry is the unstable supply of raw materials and the resulting increased collection radius, which have a large effect on the sustainability performance of biomass direct-fired power systems in terms of emergy indicators.